Biogenic Amines in Italian Pecorino Cheese - Schirone, Maria; Tofalo, Rosanna; Visciano, Pierina; Corsetti, Aldo; Suzzi, Giovanna (Frontiers in Microbiology, 2012)
The quality of distinctive artisanal cheeses is closely associated with the territory of production and its traditions. Pedoclimatic characteristics, genetic autochthonous variations, and anthropic components create an environment so specific that it would be extremely difficult to reproduce elsewhere. Pecorino cheese is included in this sector of the market and is widely diffused in Italy (∼62.000t of production in 2010). Pecorino is a common name given to indicate Italian cheeses made exclusively from pure ewes’ milk characterized by a high content of fat matter and it is mainly produced in the middle and south of Italy by traditional procedures from raw or pasteurized milk. The microbiota plays a major role in the development of the organoleptic characteristics of the cheese but it can also be responsible for the accumulation of undesirable substances, such as biogenic amines (BA). Bacterial amino acid decarboxylase activity and BA content have to be investigated within the complex microbial community of raw milk cheese for different cheese technologies. The results emphasize the necessity of controlling the indigenous bacterial population responsible for high production of BA and the use of competitive adjunct cultures could be suggested. Several factors can contribute to the qualitative and quantitative profiles of BA’s in Pecorino cheese such as environmental hygienic conditions, pH, salt concentration, water activity, fat content, pasteurization of milk, decarboxylase microorganisms, starter cultures, temperature and time of ripening, storage, part of the cheese (core, edge), and the presence of cofactor (pyridoxal phosphate, availability of aminases and deaminases). In fact physico-chemical parameters seem to favor biogenic amine-positive microbiota; both of these environmental factors can easily be modulated, in order to control growth of undesirable microorganisms. Generally, the total content of BA’s in Pecorino cheeses can range from about 100–2400 mg/kg, with a prevalence of toxicologically important BA’s, tyramine and histamine. The presence of BA is becoming increasingly important to consumers and cheese-maker alike, due to the potential threats of toxicity to humans and consequent trade implications.